2021
DOI: 10.1186/s41235-021-00337-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of implicit racial bias on recognition of other-race faces

Abstract: Previous research has established a possible link between recognition performance, individuation experience, and implicit racial bias of other-race faces. However, it remains unclear how implicit racial bias might influence other-race face processing in observers with relatively extensive experience with the other race. Here we examined how recognition of other-race faces might be modulated by observers’ implicit racial bias, in addition to the effects of experience and face recognition ability. Caucasian part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
8
1
Order By: Relevance
“…In contrast, positive social evaluation information, similar to the effect of positive emotions (Chen & Cheung, 2021;Curby et al, 2012;Xie & Zhang, 2016), may prompt observers who have little experience with the out-groups to further engage holistic processing when recognizing those faces. Importantly, note that experience and implicit social bias do not necessarily account for the same variance in the processing of out-group faces (Trawiński et al, 2021). In particular, we observed no significant correlations between experience with an out-group and implicit social bias toward the specific group in either experiment.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In contrast, positive social evaluation information, similar to the effect of positive emotions (Chen & Cheung, 2021;Curby et al, 2012;Xie & Zhang, 2016), may prompt observers who have little experience with the out-groups to further engage holistic processing when recognizing those faces. Importantly, note that experience and implicit social bias do not necessarily account for the same variance in the processing of out-group faces (Trawiński et al, 2021). In particular, we observed no significant correlations between experience with an out-group and implicit social bias toward the specific group in either experiment.…”
Section: Discussioncontrasting
confidence: 73%
“…The current study has expanded a growing literature on the influence of implicit social bias on face recognition (Lebrecht et al, 2009;Walker & Hewstone, 2008;Trawiński et al, 2021) by demonstrating its effect on holistic processing of other-race and other-age faces. It is important to note, however, that even though holistic processing is critical for face recognition, other types of processing, such as featural processing of individual components on a face (e.g., when only the eyes are available), also contribute to successful face recognition.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the future, it will be important to collect demographic information from the participants as well as to diversify the pool of stimuli under examination so that patterns such as cross-race bias effects can be explored. For example, is the face RWI effect reported here affected by the cross-race bias (e.g., Trawiński et al, 2021)?…”
Section: Limitationsmentioning
confidence: 97%
“…Individuals have varying degrees of implicit racial bias based on their own experiences and exposures in the community, and research has shown that these biases can positively or negatively influence various assessments of own-race and other-race faces, including categorization and identification. [29][30][31] To minimize these potential effects in our study, race/ethnicity designations were cross-checked by at least two members of a diverse research team. Furthermore, this data collection method has been utilized in existing literature and was similarly employed in the present study.…”
Section: Limitationsmentioning
confidence: 99%